Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Dinas Perikanan Kabupaten Lebak - Mohamad Yusup Zaelani, Jaya; Krisyanto, Edy (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. The objective of this research is to determine the partial and simultaneous influence of Motivation and Work Discipline on the performance of employees at the Lebak Regency Fisheries Department. This research employs a quantitative descriptive method to objectively examine a situation using numerical data collected through questionnaires. The sample used was a non-probability sampling with a saturated sampling technique from 52 employees. Data analysis was conducted using the hypothesis testing method with SPSS version 26. The results showed that both Motivation and Work Discipline variables have a significant influence on the performance of employees at the Lebak Regency Fisheries Department, both partially and simultaneously. Based on partial statistical tests or t-tests, the calculated t- value of 1.859 is greater than the critical t-value of 2.009. This means that H1 is accepted and H01 is rejected. Therefore, it can be concluded that Motivation has a significant impact on employee performance. Meanwhile, for Work Discipline, the calculated t-value of 3.476 is greater than the critical t-value of 2.006. This means that H2 is accepted and H02 is rejected. Therefore, it can be concluded that Work Discipline has an impact on employee performance. Simultaneously, the calculated F-value of 64.430 is greater than the critical F-value of 3.19 with a significance level of 0.000 < α 0.05, indicating that H03 is rejected and Ha3 is accepted. This means that Motivation and Work Discipline have a significant influence on employee performance. These findings suggest that the influence of Motivation and Work Discipline on employee performance is influenced or explained by other variables outside of those examined in this study. Keywords: Motivation, Work Discipline, Performance